Towards a Theology of HIV / AIDS - Wyngaard, Arnau Van (Verbum et Ecclesia, 2006)
In a world which is slowly but surely being devastated by the HIV / AIDS pandemic, the church needs to get involved in the fight against this disease. In many places the church has conveniently denied that HIV / AIDS has anything to do with them. In this paper the author argues for the necessity of thinking theologically about the reality of HIV / AIDS , indicating that HIV / AIDS is not merely a matter of "sinners" becoming infected with a virus, but that certain circumstances are conducive towards the spreading of HIV / AIDS which need to be addressed if an impact is to be made on the spreading of the virus. Although many non-religious organisations are fighting this disease, the church is in an ideal situation to assist these bodies as it is already grounded within communities and already have integrity amongst a large part of the population. However, to achieve this goal the churches must be transformed in the face of the HIV / AIDS crisis, in order that they themselves may become a force for transformation - bringing healing, hope, and accompaniment to all infected with and affected by HIV / AIDS.
Free